2013
DOI: 10.1016/j.jfca.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compound composition in immature seeds of fava bean (Vicia faba L.) varieties cultivated in Chile

Abstract: Artículo de publicación ISIFava beans (Vicia faba L.) are a popular food in many countries. However, there is a lack of information about the phenolic composition of some important edible varieties. Polyphenols in fava beans are located in several parts of the plant (e.g. leaves, roots and seeds) but their occurrence in immature seeds is most important for human nutrition. The objective of this work was to study the phenolic composition of the major groups of polyphenols in 10 varieties of immature fava be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 32 publications
7
64
3
1
Order By: Relevance
“…Total phenolic concentration of the seeds was higher than that of the stems (P <0.01), though the concentrations of the stems and seeds were lower than those reported for Vicia fava L. (Baginsky et al, 2013), Onopordon acanthium L. seeds (Zare et al, 2014), Trigonella foenum graecum seeds (Seasotiya et al, 2014) and Albizia lebbeck and Cicer arietinum seeds (Imran et al, 2014). Total phenolic concentrations of J. acutus seeds and stems were higher than those reported for some varieties of potatoes (Solanum tuberosum L.) (Hesam et al, 2012).…”
Section: Stem (N = 20)mentioning
confidence: 77%
“…Total phenolic concentration of the seeds was higher than that of the stems (P <0.01), though the concentrations of the stems and seeds were lower than those reported for Vicia fava L. (Baginsky et al, 2013), Onopordon acanthium L. seeds (Zare et al, 2014), Trigonella foenum graecum seeds (Seasotiya et al, 2014) and Albizia lebbeck and Cicer arietinum seeds (Imran et al, 2014). Total phenolic concentrations of J. acutus seeds and stems were higher than those reported for some varieties of potatoes (Solanum tuberosum L.) (Hesam et al, 2012).…”
Section: Stem (N = 20)mentioning
confidence: 77%
“…Immature faba bean seeds (fresh or frozen) are a favored vegetable in many countries. Like other food legumes, faba bean contains numerous phytonutrients, such as vitamins, minerals and phenolics, which contribute to the overall antioxident activities of plant foods (Oomah et al, 2011;Baginsky et al, 2013). Faba bean provides an alternative to soybean meal for animal feed in temperate regions where soybean cannot be grown.…”
Section: Crop Faba Bean (Vicia Faba L)mentioning
confidence: 99%
“…This shows TiCl 4 interacts with phenolic compounds and possibly also with tannins in the seed coats of fresh cotyledons of CDC Fatima. Baginsky et al (2013) reported significant amounts of phenolic compounds (anthocyanins, flavonoids and other compounds structurally similar to V-C) in immature faba bean seeds. Our analytical studies (not published) done later showed significant amounts of phenolic compounds (for example, cathechin) in normaltype flowers of V. faba (Ferhatoglu et al, unpublished).…”
Section: Ticl 4 Assay Re-evaluation Modificationmentioning
confidence: 99%
“…Immature faba beans used as vegetable are a significant source of vitamin A (350 iU per 100 g) and vitamin C (0.033%) (http://www.nal.usda.gov/fnic/foodcomp/search, Kmiecik et al, 1990) and polyphenols with antioxidant activity (Baginsky et al, 2013). Green pods of faba bean are a significant source of L-DOPA (Burbano et al, 1995) which is used for treating Parkinson disease (Seeberger and Hauser, 2009) and for overcoming low libido in human (Hulse, 1994).…”
Section: Introductionmentioning
confidence: 99%